2009
DOI: 10.1016/j.ydbio.2009.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a mechanochemical checkpoint and negative feedback loop regulating branching morphogenesis

Abstract: Cleft formation is the initial step in submandibular salivary gland (SMG) branching morphogenesis, and may result from localized actomyosin-mediated cellular contraction. Since ROCK regulates cytoskeletal contraction, we investigated the effects of ROCK inhibition on mouse SMG ex vivo organ cultures. Pharmacological inhibitors of ROCK, isoform-specific ROCK I but not ROCK II siRNAs, as well as inhibitors of myosin II activity stalled clefts at initiation. This finding implies the existence of a mechanochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
146
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(158 citation statements)
references
References 58 publications
12
146
0
Order By: Relevance
“…To directly assess effects of inhibitors on the epithelium, epithelial rudiments must be cultured in the absence of mesenchyme in either Matrigel or laminin-111 gels 6,7 . Small inhibitory RNAs (siRNAs) are an effective method to down-regulate epithelial gene expression since siRNAs are preferentially taken up by the epithelial cells in the presence of most lipid carriers 13,14,17,18 . However, neither of these methods for interfering with protein levels or function allow overexpression of a wild-type or mutant gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To directly assess effects of inhibitors on the epithelium, epithelial rudiments must be cultured in the absence of mesenchyme in either Matrigel or laminin-111 gels 6,7 . Small inhibitory RNAs (siRNAs) are an effective method to down-regulate epithelial gene expression since siRNAs are preferentially taken up by the epithelial cells in the presence of most lipid carriers 13,14,17,18 . However, neither of these methods for interfering with protein levels or function allow overexpression of a wild-type or mutant gene.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike 4% PFA, 2% PFA will preserve a significant amount of the GFP signal if the fixative is completely removed after fixation. Glands can be stored for up to 1 week in 1X PBS in the dark at 4 °C until whole mount immunocytochemistry and confocal imaging is performed, as reported previously 3,6,[13][14][15] . Ideally, immunocytochemistry and imaging should be performed soon after fixation to obtain the best quality images.…”
mentioning
confidence: 99%
“…Since ROCK and myosin inhibition prevented cleft progression, but not cleft initiation, our previous results suggested that ROCK-stimulated myosin activity is required for the transition of initiated clefts to a progression-competent state (Daley et al, 2009). Such a finding is consistent with a role for ROCK and myosin in the stabilization of already initiated clefts, and is supported by earlier observations demonstrating that cleft initiation in the salivary gland is a dynamic event, with some clefts becoming stabilized at the epithelial surface, while others rapidly disappear (Nogawa, 1983;Larsen et al, 2006).…”
Section: Introductionmentioning
confidence: 89%
“…We recently demonstrated that Rho kinase (ROCK 1)-mediated actomyosin contraction is the upstream signal that drives FN assembly during SMG cleft progression (Daley et al, 2009). ROCK promotes cytoskeletal contraction by enhancing the activation of myosin light chain 2 (MLC2), both directly through phosphorylation on Ser19 Totsukawa et al, 2000) and indirectly by phosphorylating and inactivating the myosin binding subunit of myosin light chain phosphatase Feng et al, 1999;Kawano et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The key regulator which provides a mechanistic link between fibronectin and cleft propagation has recently been identified as BTB (POZ) domain containing 7 (Btbd7) (Onodera et al , In Press). Interestingly, inhibiting cellular contractility by blocking Rho-associated coiled-coil containing kinase (ROCK) I or non-muscle myosin II prevents cleft progression and freezes clefts in an early, unstable state (Daley et al , 2009). The authors suggest that at this stage, there is a “mechanochemical” checkpoint during which transition of clefts to a stabilized form is achieved through ROCK-dependent assembly of fibronectin and potentially fibronectin-induced epithelial proliferation (Figure 2).…”
Section: Mechanical Forces Generated By the Extracellular Matrix (Ecm)mentioning
confidence: 99%